What we were made for : - Wheeler, Sondra Ely (Jossey-Bass, 2007)
Not a devotional or inspirational book, What We Were Made For is a wide-ranging and wise exploration of love in Christian life that offers a deeper understanding of this fundamental gift and calling. Throughout this provocative book, Sondra Wheeler poses challenging questions and offers new insights and considerations of what love means as a central part of Christian faith. Drawing on the long tradition of Christian thought and practice, Wheeler explores what love is, and how we know; why and how it so often goes awry; what its healing might require, and what it might make possible.